Effect of lithium phosphate on the structural and electrochemical performance of nanocrystalline LiFePO4 cathode material with iron defects. (25th January 2018) - Wu, Yan-Jie; Gu, Yi-Jie; Chen, Yun-Bo; Liu, Hong-Quan; Liu, Cheng-Quan
Abstract: The influence of excessive lithium on the crystal structure, morphology, and electrochemical properties of Fe-deficient Li x FePO4 ( x  = 1.00, 1.02, 1.04, 1.05) cathode material was investigated using co-precipitation and the carbon thermal method. The X-ray diffraction pattern and Rietveld refinement results show that excessive Li + combines with the phosphate group to form Li3 PO4 rather than occupying the Fe site to form antisite pairs. Benefitting from the intrinsic ion conductivity of lithium phosphate, the lithium diffusion coefficient of Li x FePO4 increases. However, the charge transfer impedance (Rct) also increases with increasing Li content due to the presence of Li3 PO4, a nonconductive phase that can block the electric transfer channel. The biphasic Li x FePO4 ( x  = 1.02) compound shows the best performance. This work suggests an effective and easy way to improve the electrochemical performance by adding excessive Li, which leads to the formation of Li3 PO4 . Highlights: Li x FePO4 ( x  = 1.00) sample is a single crystal structure with iron deficiency. The excessive Li + forms Li3 PO4 phase through combination with the phosphate group. Li3 PO4 increases the DLi+ and Rct due to ionic and non-conductivity, respectively. The rate performance is enhanced due to second phase Li3 PO4 . The Li x FePO4 ( x  = 1.02) composite material with Fe-deficient performs best.